2016
DOI: 10.1002/gps.4423
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid deposition in semantic dementia: a positron emission tomography study

Abstract: BackgroundPittsburgh compound B ([11C]‐PIB) identifies amyloid‐β (Aβ) deposition in vivo. Asymptomatic Aβ deposition has been reported consistently in some healthy older subjects. Of patients with frontotemporal dementia, those who have later onset have a higher potential for Aβ deposition.ObjectiveComparison of Aβ deposition in Alzheimer's disease (AD), healthy older controls, and patients with early‐ and late‐onset semantic dementia (SD), a subtype of frontotemporal dementia.MethodsSubjects were recruited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(61 reference statements)
1
6
1
Order By: Relevance
“…However, svPPA patients with biological profile of AD are very rare. The percentage of svPPA-AD in our series (14%) is absolutely in line with previous studies revealing AD pathology in svPPA [6][7][8][9][10][13][14][15]19,[24][25][26][27][28][29] (Table 1). Moreover, we acknowledge that it would be preferable to have FDG-PET data for a better spatial resolution and sensitivity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, svPPA patients with biological profile of AD are very rare. The percentage of svPPA-AD in our series (14%) is absolutely in line with previous studies revealing AD pathology in svPPA [6][7][8][9][10][13][14][15]19,[24][25][26][27][28][29] (Table 1). Moreover, we acknowledge that it would be preferable to have FDG-PET data for a better spatial resolution and sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…This second hypothesis would imply that late-onset svPPA might be more frequently associated with amyloid pathology than early-onset svPPA. A recent amyloid PET study in svPPA does not corroborate this hypothesis [24]. Moreover, two of our svPPA-AD patients have a disease onset before the age of 60 years, which cannot be considered as late-onset.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Recent molecular PET imaging studies have produced some interesting findings in SD. Firstly, amyloid PET studies have shown that a high proportion, in fact up to 30%, of SD patients can have beta-amyloid deposition in their brains [159][160][161][162][163] . The presence of betaamyloid deposition does not appear to influence the clinical presentation of SD, although the patients with beta-amyloid tend to be older 163 .…”
Section: Semantic Dementiamentioning
confidence: 99%